Effects of the moderating role of trendiness on brand image, E-WOM, brand attitude and online purchase intention - Maharramov, Rashad; Huseynli, Bahman; Kandemir Çomoğlu, Gözde (Business, Management and Economics Engineering, 2026)
Purpose – The purpose of the research is to analyse the impact of electronic word-of-mouth (e-WOM), brand image, and consumer attitude on purchase intention, as well as the moderating influence of trendiness on these relationships. Research methodology – The study is quantitative research. Six hypotheses were put forward and tested in the research model. Survey data derived from a sample of 922 participants from Azerbaijan were examined using SPSS in order to evaluate the hypothesis. Findings – According to the main findings, regression tests, it was determined that e-WOM, brand image and attitude towards the brand affect online purchasing intention. However, for the first time in this study, the moderator role of the trendiness variable, which was tested statistically, on the effect of e-WOM, brand image and attitude variables on online purchase intention was carried out. As a result of the analysis, although the moderator role of trendiness in the effect of e-WOM’s online purchase intention and brand image on online purchase intention was found to be significant and positive, the moderator role of trendiness in the effect of attitude on online purchase intention was found to be insignificant. Research limitations – The study exclusively covers Azerbaijan’s fast-food service industry. Also, different people may have different ideas about fast food places, and the brand names in the questions may affect how people answer. Practical implications – This study’s scientific innovation is the first statistical test of the moderating role of the trendiness variable in the effects of e-WOM, brand image, and attitude on online purchase intention. Practical innovation is that data specific to the Azerbaijani fast-food sector can be useful for practitioners in helping brand managers better understand consumer behaviour and develop trend-focused marketing strategies. Originality/Value – This research makes a major addition to was proved for the first time in the literature that the trendiness variable affects the brand’s images and e-WOM even if it does not affect the attitude-to-purchase orientation. In this study, trendiness was found to strengthen the relationships between e-WOM, consumer perceptions of brands, and intent to buy, which reveals a new relationship not found in the existing literature. However, fast-food consumption habits of Azerbaijani consumers were also determined by a large survey.